Caracterização estrutural e morfológica de cobatilte de zinco obtido via método de sol-gel protéico - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Transition metal oxides are a group of materials that have been synthesized in the namometric scale because they have different possibilities of applications in various fields of industry. There are many methods of synthesis used to obtain nanoparticles. Among the oxides, the Zinc Cobaltite (ZnCo2O4) has been of great research because it is considered a material of great potentiality due to its characteristics of improved reversible capacities, improved cycling stability, good environmental benignity and low cost. In this work, the Zinc Cobaltite was synthesized by the sol-gel protein method using edible gelatin as the precursor, whose calcination of the samples was at temperatures of 400 and 800 ° C. In addition, the material was characterized by x-ray diffraction, refined by the Rietveld method and observed the surface of the sample by scanning electron microscopy. By the analysis of the diffractograms it was verified that the samples have crystalline structure ofthe spinel type, where the sample calcined at 400 ° C presented crystalline phases of ZnO and ZnCo2O4 and amorphous phase, and the sample calcined at 800 ° C presented only phases of ZnO and ZnCl2O4. Through the Rietiveld Refinement, it was possible to determine the parameters of the crystalline structure of the material, whose crystallite diameter decreased with increasing calcination temperature. Analyzing the micrographs we can observe in the sample ZnCo2O4 / ZnO calcined at 400 ° C the distribution of micro-octahedrons deposited in matrix of amorphous (carbonaceous) material and the micrography of the sample ZnCo2O4 / ZnO calcined at 800 ° C shows that the particles approach a spherical shape showing grain distribution in uniform size. All data obtained show that the synthesis parameters are extremely important for the formation of a material with singular properties, where it can be applied for specific purposes.
Keywords: Síntese; Sol-gel; Cobaltita de zinco; Material; Nanopartículas